The Effect of Neonatal Leptin Antagonism in Male Rat Offspring Is Dependent upon the Interaction between Prior Maternal Nutritional Status and Post-Weaning Diet. (2nd April 2012) - Beltrand, J.; Sloboda, D. M.; Connor, K. L.; Truong, M.; Vickers, M. H.
Abstract : Epidemiological and experimental studies report associations between overweight mothers and increased obesity risk in offspring. It is unclear whether neonatal leptin regulation mediates this association between overweight mothers and offspring obesity. We investigated the effect of neonatal treatment with a leptin antagonist (LA) on growth and metabolism in offspring of mothers fed either a control or a high fat diet. Wistar rats were fed either a control (CON) or a high fat diet (MHF) during pregnancy and lactation. Male CON and MHF neonates received either saline (S) or a rat-specific pegylated LA on days 3, 5, and 7. Offspring were weaned onto either a control or a high fat (hf) diet. At day 100, body composition, blood glucose, β -hydroxybutyrate and plasma leptin and insulin were determined. In CON and MHF offspring, LA increased neonatal bodyweights compared to saline-treated offspring and was more pronounced in MHF offspring. In the post-weaning period, neonatal LA treatment decreased hf diet-induced weight gain but only in CON offspring. LA treatment induced changes in body length, fat mass, body temperature, and bone composition. Neonatal LA treatment can therefore exert effects on growth and metabolism in adulthood but is dependent upon interactions between maternal and post-weaning nutrition.